The quality of semi-finished steel - A. G. Anisovich (Литьë и металлургия)
The article deals with the quality of structural steel supplied by metallurgical enterprises. It is shown that the pipes made of steel 20, used in the oil and gas industry, contain structurally free cementite in the structure, often in the form of a grid (points 4 and 5 according to GOST 5640–68). This structure is the cause of faulty production: the subsequent cold treatment pressure formed sags on the surface of the product, and there is a violation of the continuity of the material up to the formation of through cracks. Formation of structurally-free cementite in steel 40KHN2MA with structure of the top bainite which was formed at violation of regulations of heat treatment of a semi-finished product is also found. When nitriding with heating to 490 ° C and holding at this temperature, there was a decay of bainite with the formation of tertiary cementite along the grain boundaries. Discussed the possibility of culling the poor quality of delivery at the consumer. It is also noted that many enterprises have now abolished entrance control, which has the most negative consequences both in terms of product quality and safety, especially in the oil and gas industry.